Adipokines and ghrelin in gastric cancer cachexia - Mustafa Kerem; Zafer Ferahköşe; Utku Yılmaz; Hatîce Paşaoğlu; Ebru Ofluoğlu; Abdülkadir Bedirli; Bülent Salman; Tevfik Tolga Şahin; Murat Akın (2008)
AIM:To investigate the roles of the adipocytokines, ghrelin and leptin in gastric cancer cachexia.METHODS: Resistin, ghrelin, leptin, adiponectin, insulin and insulin-like growth factor (IGF-Ⅰ), were measured in 30 healthy subjects, and 60 gastric cancer patients of which 30 suffered from cancerinduced cachexia and 30 served as a control group.The relationships between hormones, body mass index (BMI) loss ratio, age, gender, and Glasgow Prognostic Score (GPS) were investigated.RESULTS: Cachexia patients had higher tumor stage and GPS when compared with non-cachexia patients (P < 0.05).Ghrelin, resistin, leptin, adiponectin and IGF-Ⅰ, showed a significant correlation with BMI loss ratio and GPS (P < 0.05).A strong correlation was seen between GPS and BMI loss (R = -0.570,P < 0.0001).Multivariate analysis indicated that BMI loss was significantly independent as a predictor of ghrelin, resistin, leptin and IGF-Ⅰ (P < 0.05).Existence of an important significant relationship between resistin and insulin resistance was also noted.CONCLUSION: These results showed that serum ghrelin, leptin, adiponectin, and IGF-Ⅰ play important roles in cachexia-related gastric cancers.No relationship was found between resistin and cancer cachexia.Also, because of the correlation between these parameters and GPS, these parameters might be used as a predictor factor.